Simulation of the extra-terrestrial and terrestrial performance of GaAs/Ge dual-junction solar cells - Sumaryada, Tony; Afgan Sofyan; Heriyanto Syafutra (Kuwait Journal of Science, 2019)
The performance of GaAs/Ge dual-junction solar cells in the extra-terrestrial and terrestrial condition are studied by means of the full simulation approach. Simulations consist of solar radiation modeling and the electronic transport modeling of each subcell. Simulation result shows that the efficiency of the solar cells in extra-terrestrial condition is 31.91%, while in terrestrial condition is 35.24%. Although the efficiency in extra-terrestrial condition is lower, due to a larger amount of incident solar radiation on the first subcell (GaAs), the total power produced in extra-terrestrial condition is higher as compared to second subcell (Ge). It is found that for 1.0 m2 area of GaAs/Ge solar panel, about 419.2 Watt of power is produced in extra-terrestrial condition as compared to 314.34 Watt in terrestrial condition.